Long-term Mechanical Properties and Microstructure of Concrete Utilizing Self-Cementing Fly Ash as A Sole Binder Material - Oswyn Karsten Wattimena; Antoni Antoni; Djwantoro Hardjito (Civil Engineering Dimension, 2023)
Self-cementing fly ash, containing calcium oxide (CaO) of about 20%, has successfully become a sole binder material in concrete through hydration. A very low water-to-fly ash ratio, e.g., below 0.20, is the main key to achieving the high compressive strength of concrete. This study explores the strength evolution, long-term compressive strength, and mechanical properties of concrete that utilize self-cementing fly ash as a sole binder material. Remarkably, the long-term compressive strength continues to develop over a year, reaching nearly 50 MPa at 365 days, a 34% increase from the 28-day strength. While the other mechanical properties are slightly lower than predictions from empirical formulas for Portland cement concrete, promising results are observed. Scanning Electron Microscope (SEM) images highlight surface-restricted hydration products in self-cementing fly ash, rather than full dissolution of fly ash particles.